Developing a toolkit to help smaller local authorities establish strong net zero governance in the UK - Gudde, Peter; Bury, Nicolas; Cochrane, Peter; Caldwell, Nicholas (Frontiers in Sustainable Energy Policy, 2024)
Introduction The Skidmore Review of UK Government's net zero approach highlights a lack of a national framework which establishes local government role, responsibilities and area-based governance arrangements. Although unified political leadership agreed as part of devolution deals has helped some areas to marshal resources and support, the national delivery landscape for net zero remains patchy. This study develops a toolkit to help local areas improve local arrangements. Methods A mixed methods research approach has been used to develop the toolkit. It incorporates a set of governance models, a method for assessing the values of good governance, a governance improvement process and an illustration of how the toolkit can be employed using three cases where the two-tier public administrative structure applies. Results Results from the research process suggest that although change is happening it lacks the coherence and scale needed, with non-urban multiple-tier public administrations getting left behind by their metropolitan, single-tier counterparts creating a credibility and performance gap between political rhetoric and local net zero delivery. This observed inertia highlights the need to change governance processes and practices if public administration is going to deliver its part of net zero effectively outside the UK Metropolitan areas. Discussion The gap in support for local government to develop net zero governance arrangements is well recognized in both this research and publicly funded research programmes. This study provides UK local authorities with a simple, effective toolkit, that could potentially help them build strong wider societal relationships that will assist them in playing their full part in the UK reaching net zero.